English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i keep getting the wrong answer

6(3x-4)-(1-3x)=-67
18x-24-1-3x=-67
15x-25=-67
+25 +25
15x=-42
x=-2.8
the asnwer is supposed to be -2
is wat i did right or wrong. if its wrong how do you do it?

2007-01-02 09:52:47 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

When you distribute the negative sign through, it should be +3x

6(3x - 4) - (1 - 3x) = -67
18x - 24 - 1 + 3x = -67 <-- Here's the corrected step
21x - 25 = -67
21x = -42
x = -42/21
x = -2

2007-01-02 09:55:12 · answer #1 · answered by Puzzling 7 · 2 0

You're supposed to multiply -1 times 1 and -3x:
18x-24-1+3x=-67
21x-25=-67
21x=42
x=2

2007-01-02 18:04:13 · answer #2 · answered by jacobandalex 2 · 0 0

18x-24-1+3x= -67
21x -25= -67
21x = - 42
x = - 2

2007-01-02 17:58:17 · answer #3 · answered by Piguy 4 · 0 0

6(3x-4)-(1-3x)=-67
18x-24-1-3x=-67 xxxxx it's +3X

18x-24-1+3x=-67
21x=-42
x=-2

2007-01-02 17:57:32 · answer #4 · answered by DKidd 2 · 0 0

You messed up one step. -(1 - 3x) is not -1 - 3x, but rather it is -1 + 3x. So 6(3x-4)-(1-3x)= 18x-24-1 + 3x = 21x - 25.

2007-01-02 17:57:29 · answer #5 · answered by Edgar Greenberg 5 · 0 0

i think u r right

2007-01-02 17:57:00 · answer #6 · answered by well thts it...... 3 · 0 0

fedest.com, questions and answers